Hepatitis E-related adverse pregnancy outcomes and their prevention by hepatitis E vaccine in a rabbit model. Issue 1 (1st January 2019) - Li, Manyu; Li, Shuangshuang; He, Qiyu; Liang, Zhaochao; Wang, Lin; Wang, Qianhui; Wang, Ling
ABSTRACT: Hepatitis E virus (HEV) can lead to high mortality during pregnancy. This study was to investigate the adverse pregnancy outcomes caused by different HEV genotypes and their prevention by HEV 239 vaccine in rabbits. Forty-two female rabbits were randomly and equally divided into 7 groups (A-G). HEV 239 vaccine and a placebo were administered to groups E (10 μg×2), F (5 μg×2) and G (1 mL of PBS×2) before copulation. After pregnancy, 1 mL of 1.5×106 copies/mL rabbit HEV3 was inoculated to groups A, E, F and G, swine HEV4/human HEV3 to groups B/C, and group D was a negative control. Anti-HEV antibody, HEV RNA, and alanine aminotransferase (ALT)/aspartate aminotransferase (AST) levels were monitored. Pregnant rabbits infected by HEV manifested HEV infection symptoms including fecal virus shedding, ALT/AST elevation, and histopathological changes, and adverse pregnancy outcomes. Immunized pregnant rabbits in groups E and F showed no HEV infection symptoms and adverse outcomes. The newborn rabbits delivered by pregnant rabbits with/without immunization showed without/with HEV infection symptoms. This study demonstrated that multiple genotypes of HEV infection can cause adverse outcomes and HEV 239 vaccine can prevent HEV-related adverse outcomes in pregnant rabbits.